(untitled) (Boston, MA., 2006)
The purpose of English for Professional Success is to empower students with the language and life skills they need to carry out their career goals. To this end it provides ample opportunities for students to build awareness and practice the language in real-life scenarios. Its integrated skills approach develops the student’s self-confidence to survive and succeed in professional and social encounters within an English-speaking global community. University students regardless of their major will immediately be motivated by the opportunity to prepare for the job market as they practice their English language skills in the following job-related scenarios. Professional development Continuing education, graduate school, distance learning, student employment, and performance evaluation Job hunting How to read want ads, deal with application forms, plan and write cover letters and resumes, develop interview skills and learn what employers look for in a candidate Relocating Apartment hunting, deciding whether or not to look for a roommate and how to do so, handling landlords, interpreting leases, dealing with household problems On the job skills Problem-solving, setting goals, creating action plans, decision-making, developing time-management skills, dealing with change within a company The language of work Learning the language of warehousing, placing orders, participating in meetings, giving formal presentations, practicing moderating skills
Keywords: English language,Business English; Texbooks for foreign speakers